Fostering Empathy and Innovation: Implementing Arts-Based Methods (ABMs) within Student-Centered Learning Frameworks in Higher Education - Eneng Martini; Didi Sudrajat; A. Fitriani; Armita Permatasari; Muh. Safar (PT Inovasi Pratama Internasional, 2026)
Empathy and innovation are increasingly recognized as core graduate attributes in higher education, yet conventional lecture-centered pedagogies often struggle to cultivate these complex capacities. This quantitative study investigates the effectiveness of integrating Arts-Based Methods (ABMs) within a student-centered learning framework to foster empathy and innovation among undergraduate students in a social sciences program. Drawing on prior research that demonstrates the potential of arts and humanities education to enhance empathic skills and perspective taking, the study employs a quasi-experimental pretest–posttest control group design in a compulsory semester-long course. A total of 182 students were assigned to either an ABM-integrated, student-centered condition or a conventional student-centered condition without arts integration. Standardized instruments were used to measure multidimensional empathy and self-reported innovative behavior. Descriptive statistics, independent samples t-tests, and multiple regression analyses were conducted. Results indicate that students in the ABM condition showed significantly greater gains in perspective taking, empathic concern, and self-reported innovation than peers in the comparison group, even after controlling for gender, prior artistic engagement, and baseline scores. Findings suggest that ABMs, when systematically embedded within student-centered learning, can create participatory, reflective, and emotionally rich learning environments that support the development of empathic and innovative dispositions in higher education